Loyalitas: Seberapa Pentingkah bagi ASN di Era Pandemi COVID-19 ? - Diana Setyawati; Abu Talkah; Eka Askafi (Universitas Islam Kadiri, 2022)
The never-ending COVID-19 pandemic has had a tremendous impact on the global realm. All industrial and office sectors in Indonesia also feel the influence. Especially in the management of human resources clearly has a great importance in this era of the COVID-19 pandemic. Like the judiciary in Indonesia, which is in a dilemma, on the one hand, it must obey dynamic government regulations in order to accelerate the handling of the COVID-19 pandemic, but on the other hand, it must maintain loyalty as human resources who are involved in judicial institutions with demands for implementation. (eight) main values of the supreme court. This research was conducted with the aim of looking at how and what factors can affect the increase in the loyalty of an employee within the judiciary of the Republic of Indonesia. This study uses a descriptive quantitative approach with the completion of path analysis. The results obtained in this study are concrete evidence that shows a direct influence between the independent variable and the dependent variable, but this study did not succeed in proving an indirect effect through the mediating variable.